Consumers' Intention to Use Drone Food Delivery Services: Investigating Technological Beliefs, Desire, and Perception towards AI-Enabled Personalisation - Ling, Alvin Han Ming (Curtin University, 2024)
This thesis explores the potential of drone food delivery services (DFDS) in Malaysia, highlighting their safety, speed, and environmental benefits. Using the belief-desire-intention model, Technology Readiness Index, and Expectancy Theory, this study investigated how consumer beliefs and perceptions of AI-enabled personalization influence their desire, leading to intentions to use DFDS. These insights align with Malaysia's technological visions and sustainability goals, offering valuable strategies for promoting DFDS adoption and contributing to global sustainable development objectives.